Evaluation of the stability of the Caesalpinia spinosa extract under stress-induced conditions. - Guzmán Méndez, Daniela Valentina; Modesti Costa, Geison (Revista Productos Naturales, 2022)
An extract obtained from Caesalpinia Spinosa, has been investigated for several years on the PUJ, because of its therapeutic potential against breast cancer.